After the Pink Slip: Applying Dynamic Motivation Frameworks to the Job Search Experience - Wanberg, Connie R.; Zhu, Jing; Kanfer, Ruth; Zhang, Zhen (Academy of Management Journal, 2012)
We propose and examine a self-regulatory framework focused on understanding the dynamics of job search intensity and mental health over the first several months of unemployment. We use a repeated-measures design, surveying newly unemployed individuals weekly for 20 weeks. Through the lens of our framework, we test relationships pertaining to the role of motivational “traits” (i.e., temporally stable approach and avoidance motivations) and self-regulatory “states” (i.e., more transient motivation control and self-defeating cognition) in predicting job seekers' search intensity and mental health over the duration of our study. The findings provide evidence on the dynamics of the job search journey.